1997
DOI: 10.1023/a:1018577127619
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Table 1 give the values of for all solvents used by Imamura and his collaborators in his various publications in this journal. It is interesting that the results of Khan et al [10] about the values of applied to copper chloro complex in various apro- Table 1 The values for dielectric constant ε and at room temperature [10]. tic solvents also seem to hold for magnesium carbon composite in THF.…”
Section: The Ratio = Mw/εmentioning
confidence: 95%
See 3 more Smart Citations
“…Table 1 give the values of for all solvents used by Imamura and his collaborators in his various publications in this journal. It is interesting that the results of Khan et al [10] about the values of applied to copper chloro complex in various apro- Table 1 The values for dielectric constant ε and at room temperature [10]. tic solvents also seem to hold for magnesium carbon composite in THF.…”
Section: The Ratio = Mw/εmentioning
confidence: 95%
“…The values of stability constantsˇj for metal complex formation increases again for greater than 60. It is interesting that Khan et al [10] observed that the values of the stability constantsˇj (j = 1, 4) for the formation of organomegnesium halides is higher for higher values of j. This was only valid when the values of is in the range from 9 to 20.…”
Section: The Ratio = Mw/εmentioning
confidence: 98%
See 2 more Smart Citations
“…[2][3][4][5][6] The formation of halogeno complexes of cobalt(II) in various solvents, such as acetone, 7 molten acetamide, 8 nitromethane and nitrobenzene, 9 has been investigated. The color change of an aqueous Co(II) solution from pink to blue upon the addition of Cl -is a wellknown phenomenon and is ascribed to the conversion of Co(H2O)6 2+ to CoCl4 2-.…”
Section: Introductionmentioning
confidence: 99%